Allyl triphenyl phosphonium bromide based DES-functionalized carbon nanotubes for the removal of mercury from water. (January 2017) - AlOmar, Mohamed Khalid; Alsaadi, Mohammed Abdulhakim; Hayyan, Maan; Akib, Shatirah; Ibrahim, Muhammad; Hashim, Mohd Ali
Abstract: Recently, deep eutectic solvents (DESs) have shown their new and interesting ability for chemistry through their involvement in variety of applications. This study introduces carbon nanotubes (CNTs) functionalized with DES as a novel adsorbent for Hg 2+ from water. Allyl triphenyl phosphonium bromide (ATPB) was combined with glycerol as the hydrogen bond donor (HBD) to form DES, which can act as a novel CNTs functionalization agent. The novel adsorbent was characterized using Raman, FTIR, XRD, FESEM, EDX, BET surface area, TGA, TEM and Zeta potential. Response surface methodology was used to optimize the removal conditions for Hg 2+ . The optimum removal conditions were found to be pH 5.5, contact time 28 min, and an adsorbent dosage of 5 mg. Freundlich isotherm model described the adsorption isotherm of the novel adsorbent, and the maximum adsorption capacity obtained from the experimental data was 186.97 mg g −1 . Pseudo-second order kinetics describes the adsorption rate order. Graphical abstract: Image 1 Highlights: Deep eutectic solvents were used as functionalization agents of CNTs. The DES-CNT combination utilized as a novel Hg 2+ adsorbent. The DESs-CNTs adsorbent were characterized by various instrumental methods. The effect of operation parameters is optimized utilizing RSM methodology. Adsorption isotherm and kinetics were comprehensively investigated.